Untersuchung zur Praktikabilität der Anästhesieeinleitung und der Stressbelastung beim Europäischen Fischotter (Lutra lutra) mit Alphaxalon und Dexmedetomidin verglichen mit der Kombination Ketamin und Dexmedetomidin - Schneider, Frauke Anna Luise (Tierärztliche Hochschule, 2012)
Twelve Eurasian Otters were randomly assigned to two groups of six otters. After premedication with intramuscular ketamine (10 mg/kg) + dexmedetomidine (25 μg/kg) (n = 6; Group KD) or alphaxalone (5 mg/kg) + dexmedetomidine (25 μg/kg) (n = 6; Group AD), anaesthesia was maintained with isoflurane for 60 minutes. For recovery Group AD received atipamezol (125 µg/kg) intramuscularly. Cardiorespiratory parameters and temperature were continuously recorded. Venous blood samples for haematolgy,blood chemistry and cortisol concentrations were taken at predetermined time intervals. Statistical analysis included Kolmogorov-Smirnov test, Student´s t-test, ANOVA, two factorial ANOVA and Dunnets t-test. Significance was set at p < 0,05. Both combinations caused adequate depth of anaesthesia to allow endotracheal intubation. Animals in group KD lost the righting reflex three minutes earlier than in Group AD. The injection volume of the combination ketamine/dexmedetomidine was lower than with the alphaxalone/dexmedetomidine combination (0,9-1,1 ml vs. 3,0-4,5 ml). In both groups cardiovascular parameters were stable and remained in a clinically acceptable range. Hypoventilation caused moderate respiratory acidosis during isoflurane anaesthesia. Quality of recovery was smooth and coordinated in group AD. Animals in group KD were sensitive to noise. Group KD regained the righting within 8 minutes after end of isoflurane supply. (9 minutes faster than group KD). However, group AD needed two times longer to acchieve sternal recumbency. All otters of group KD could be relased to their exhibit on the same day. Because of reduced activity two otters of group AD needed further surveillance for one day. In conclusion, the combination of dexemdetomidine and alfaxalone provides an alternative to ketamine combinations for induction of anesthesia in Eurasian otters. However, the larger injection volume and a possible longer recovery time to full activity has to be considered. Zwölf Europäische Fischotter wurden randomisiert in zwei ...